MODIFIKASI MANAJEMEN STRATEGIS MIN 02 KOTA TANGERANG SELATAN - Hardi, SUHARDI; Anwar, Khoirul (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2024)
This Essay presents the result of research about strategic management modification to achieve the excellences at MIN 02 South Tangerang City. From the rresearhc findings, it is derived information that MIN 02 has already implemented strategic management modification in two ways; model modification and substance modification. In the model modification, MIN 02 add the steps spiritualizing human resource amd developing learning organization. Meanwhile in the substance modification, MIN 02 changes strategic management that is empty from spiritual values into spiritual meaning and learning. Based on the management applied, then, it is found that the strategic management model developed in MIN 02 is Spiritual and Learning based Strategic Management.